Grüazi/Pfiat di/Hallöchen – ein paar Anmerkungen zur Einbindung von Sprachvarietäten in den DaF-Unterricht - Utri, Reinhold (Glottodidactica, 2014)
In the development of languages (including varieties) nationalities or countries play an important role. That is how pluricentric languages have developed. In the field of German as a pluricentric language many articles have already been published in scientific magazines. In spite of that the pluricentricity of languages is hardly acknowledged – the effects can be seen in dictionaries, in programs of teaching at universities (literature, linguistics as well as translation studies), but above all in text books for students, where elements of pluricentricity are usually absent. That is why some desiderata for the future teaching German as a Foreign Language ought to be expressed.